Women and youth in African NDCs - Huyer, Sophia (2024)
A review of gender and youth in NDCs submitted by African countries at the end of 2022 (updated in December 2024) found a high percentage of references to women and gender, as well as youth. Of a total of 53 NDCs submitted by African countries, 43 made significant references to women or gender. 37 NDCs made one or more references to youth. Gender is increasingly integrated into African NDCs, with specific connections to climate sectors including agriculture, energy, environment and livelihoods. Gender is mainstreamed in many African NDCs, showing a more integrated approach to climate policy across the continent. Most NDCs are still missing a commitment to empowerment – the focus is on women as vulnerable rather than as agents of change. Only 23 NDCs include monitoring or sex- disaggregated data collection, and only 10 commit to gender budgeting.